2013
DOI: 10.1002/jcph.215
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of tiotropium solution and tiotropium powder in chronic obstructive pulmonary disease

Abstract: The aim of the study was to characterize pharmacokinetics of tiotropium solution 5 µg compared to powder 18 µg and assess dose-dependency of tiotropium solution pharmacodynamics in comparison to placebo. In total 154 patients with chronic obstructive pulmonary disease (COPD) were included in this multicenter, randomized, double-blind within-solution (1.25, 2.5, 5 µg, and placebo), and open-label powder 18 µg, crossover study, including 4-week treatment periods. Primary end points were peak plasma concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 20 publications
4
67
1
Order By: Relevance
“…The PK profile for tiotropium delivered from TioHH in this study agrees with other published results (20). Absorption after inhalation was rapid with an average t max of 5 min.…”
Section: Discussionsupporting
confidence: 91%
“…The PK profile for tiotropium delivered from TioHH in this study agrees with other published results (20). Absorption after inhalation was rapid with an average t max of 5 min.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, there is interesting pharmacokinetic data comparing slow velocity aerosolized solution particles of tiotropium to faster velocity aerosolized powder particles, where blood exposure is lower following the slow velocity aerosol. (157) Part of this may be due to the lower nominal drug dose with the more efficient slower velocity tiotropium aerosol.…”
Section: Importance Of Aerosol Deposition Distribution To Clinical Efmentioning
confidence: 99%
“…The improved efficiency in the delivery of inhaled medication to the lung with Respimat Ò has also allowed reduction of the nominal drug dose without loss of pharmacodynamic effect or clinical efficacy in asthma and COPD [5,[36][37][38][39]. For example, clinical studies in COPD have shown the comparable bronchodilator efficacy and systemic exposure of once-daily tiotropium Respimat Ò 5 lg and tiotropium HandiHaler Ò 18 lg [38,40].…”
Section: Optimizing Drug Delivery To the Lungsmentioning
confidence: 99%